PEMBINAAN GURU UNTUK MENINGKATKAN PEMAHAMAN DALAM MENYUSUN ADMINISTRASI PERENCANAAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK - Nursani Nursani (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
Academic supervision is one of the activities carried out by principals to guide and assist teachers in learning starting from planning, implementing, and evaluating learning. Implementing learning planning administration is an obligation for every teacher so that learning takes place in an interactive, inspirational, fun, motivating students to actively participate so that it can facilitate the implementation of learning activities. The purpose of this study is to improve teacher understanding in preparing the administration of learning planning through academic supervision on teachers at MTs Negeri 2 Simeulue. This research is a School Action Research (SAR) which includes four stages of activity, namely planning, action, observing, and reflecting. The study was conducted in the odd semester of the academic year 2017/2018. The subjects in this research were 25 teachers at MTsN 2 Simeulue. Data collection techniques used were observation, interviews and documentation. Data were analyzed using descriptive analysis techniques. The results of the study showed that the percentage of mastery comprehension of the teacher in preparing the administration of learning planning was classical in the pre cycle was 52%. In the first cycle there was a 28% increase to 80%. In the second cycle, the ability of teachers to complete increased by 16% to 96%. It can be concluded that the teacher's understanding in preparing the administration of learning planning can be increased through academic supervision of teachers at MTs Negeri 2 Simeulue academic year 2017/2018.